A Visual Tool for Understanding Wicked Problems in Design Research: A Case Study of Marginalized Youth Unemployment. (15th November 2021) - Suoheimo, Mari; Tang, Tang; Juvonen, Tarja
Abstract: Design thinking has been widely embraced as an approach that fosters discussion and facilitates innovations that promote inclusion and empowerment in the public and private sectors. However, recent concerns have been expressed over its limited application and the exaggerated claims of its impacts when addressing wicked problems (WPs). A central challenge is comprehending how to support the process of simultaneously understanding WPs and acknowledging their uncertainty and risk. Through an action research project (aimed to help reduce youth unemployment by involving marginalized youths in service development in South Africa), this paper investigates the use of the Mess Mapping™ tool for collectively understanding, visualizing and aiding in decision-making related to the complexities of socially-oriented design research. We demonstrate that through a 'co-documenting, co-discovering and co-defining' process, it is possible to identify and understand the challenges and complexities that designers may encounter when informing future design research on WPs.